Analisis Wacana Kritis Sara Mills pada Film Dokumenter Ice Cold: Murder, Coffee, and Jessica Wongso - Afni, Nur; Herman, Achmad; Kudratullah (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
The purpose of this study is to determine the representation of Jessica formed in the documentary Ice Cold: Murder, Coffee, and Jessica Wongso based on Sara Mills' discourse analysis. Through a qualitative descriptive method, this discourse analyzes the subject-object position, and the position of the reader/viewer. The research subject is the movie Ice Cold: Murder, Coffee, and Jessica Wongso with the object of research is the scene that represents Jessica Wongso. The results showed that in the movie Ice Cold: Murder, Coffee, and Jessica Wongso, Jessica as the subject portrays herself as a victim of an indication of fraud in the 2016 cyanide coffee case trial. Jessica indirectly states that she is not the suspect who killed Mirna. Jessica as an object is represented with two contrasting personalities, namely negatively and positively portrayed. This movie has the potential to lead the audience's opinion to the discourse that Jessica is not a suspect in the 2016 cyanide coffee case.